Contributions of a time use perspective in community mental health practice: a scoping review - Fossey, Ellie; Doroud, Nastaran; Harvey, Carol Ann; Dun, Carolyn; Hitch, Danielle; Farnworth, Louise; Krupa, Terry (Frontiers in Psychiatry, 2024)
Time use is an important indicator of health and well-being. Exploration of time use can provide in-depth information about individuals’ activity patterns including routines and structure, the experience of activities, personal priorities and challenges. People experiencing severe mental illness may be at particular risk for time use patterns associated with poor health and wellbeing. This scoping review aimed to identify and map the evidence about how a time use perspective informs assessment and intervention in community mental health practice. Electronic databases and hand-searches were used to identify relevant studies involving people with severe mental illness, and focused on time use applications in practice. Twenty-nine studies were included in this review, data-extracted and synthesized with reference to the review question. Seven described development and psychometric testing of time use assessments; twelve used time use tools to measure outcomes; and ten described or evaluated time use intervention approaches. The identified time use assessments typically involved retrospective diaries completed before or during structured interviews, and an Experience Sampling Method using smart technology to gather activity data in real time. Both psychosocial and occupational interventions used time use to measure outcomes relevant to activity engagement, social functioning, and personal recovery. The identified time use interventions originated in occupational therapy; included structured manuals and workbooks to enable reflection on daily time use; individual or group sessions to collaborate in identifying priorities, goal planning and supporting desired changes to activity patterns. These interventions were viewed favorably overall, with improved activity engagement, quality of life, and personal recovery reported. In conclusion, time use assessments evaluate outcomes of importance to personal recovery and community inclusion. Time use interventions address activity patterns associated with poor health and wellbeing, using collaborative and supported activity engagement approaches, and contribute to emerging evidence on interventions that support personal recovery. Furthering peer involvement in developing and delivering these interventions will bring important insights to time use practice and research, while the social forces that marginalize or constrain activity participation for people with severe mental illness also need to be addressed to advance time use and other approaches that aim to support community inclusion.